The Implementation of Project Management in Community Service Programs: Impact Evaluation and Sustainability in Region Z - Nofirman, Nofirman; Thamrin, Andi; Efionita, Yolanda; Jauhari, Burhanuddin; Muriyanto, Muriyanto (International Journal of Community Service (IJCS), 2025)
This study explores the implementation of project management principles in community service programs in Region Z, aiming to evaluate their impact and sustainability. Employing a qualitative approach, data were collected through interviews, focus group discussions, and document analysis involving program managers, community leaders, and beneficiaries. The findings reveal that structured project management enhances program effectiveness, stakeholder engagement, and long-term sustainability. However, challenges such as limited resources and fluctuating community participation remain significant barriers. The study concludes that strengthening project management practices, fostering local capacity, and promoting community ownership are essential for ensuring the enduring benefits of community service initiatives in Region Z.